Solothrips brevisetis gen. et sp. nov. with a single pair of ocellar setae (Thysanoptera, Thripidae) - Li, Shenlei; Ye, Fei; Lin, Xiaojun; Cheng, Fengxian; Wang, Zhaohong; Tan, Jinfang (Zootaxa, 2025)
Among Thripinae the number and position of setal pairs around the ocellar triangle is an important diagnostic characteristic. Solothrips brevisetis gen. et sp. nov. is proposed in this paper for a species of Thripinae with only one pair of ocellar setae, instead of three or two as is usual amongst Thripinae. The intergeneric relationships are discussed based on morphological characters.